Motivation and learning strategies in accounting: Are there differences in English as a medium of instruction (EMI) versus non-EMI students? - Mª José Rivero Menéndez; Elena Urquía Grande; Pilar López Sánchez; Mª Mar Camacho-Miñano (Revista de Contabilidad: Spanish Accounting Review, 2018)
The objective of this paper is twofold: firstly, to analyse if there are differences between students’ motivation and their learning strategies when they study accounting subjects in Spanish or English as a medium of instruction. Secondly, to evidence the factors that mainly influence students’ total motivation. The Motivated Strategies for Learning Questionnaire (MSLQ) was carried out on a sample of 368 undergraduate students of a Business Administration Degree, in several accounting subjects taught in English and in Spanish. Multivariate statistical tests were run and interesting results have been found. Students who study a degree in English have more mature learning strategies and motivation than their counterparts. This is shown in their level of self-confidence, time study management and perseverance.